Characteristics of fluid‐induced resonances observed during microseismic monitoring. Issue 11 (7th November 2014) - Tary, Jean Baptiste; van der Baan, Mirko; Sutherland, Bruce; Eaton, David W.
Abstract Three groups of resonances are observed during a two‐stage hydraulic experiment recorded by 12 three‐component geophones. The injected fluid is composed of a slurry of mostly water and proppant plus some supercritical nitrogen. Resonance characteristics are estimated using an autoregressive model. Three resonance models are investigated: fluid‐filled cracks, nonlaminar fluid flow, and repetitive events in terms of anticipated resonance frequencies, quality factors, and amplitudes. The observed resonances are very stable and positively correlated with either the slurry flow or the nitrogen injection rate, which is in contradiction with the repetitive events and fluid‐filled crack models, respectively. Resonances obtained by numerical simulations of an unstable jet agree with the main characteristics of most observed resonances. Our observations suggest that variations in resonance frequencies are mainly driven by variations in fluid flow, whereas quality factors are more sensitive to the fluid composition through variations in nitrogen injection rate. This study also suggests that resonance frequencies and quality factors can provide complementary information for real‐time monitoring of fluid injection into reservoirs, for hydraulic stimulations, geothermal operations, carbon capture, and storage or fluid movement during volcano eruptions.